As noções de patologia social na teoria crítica de Axel Honneth - Leão, Luís Henrique da Costa (2022)
The academic paper consists an approach to Axel Honneth critical theory in order to situate the academic debate on social pathology notions within the scope of Social Philosophy. The aims is to explore the notion of social pathology in Axel Honneth and to understand the reactions of other authors. In order to delimit meanings, borders and transformations in the concept of social pathology in Honneth, I carry out an exploratory and bibliographical research using the works by Axel Honneth and commentators who problematize notions about Social Pathology as sources. For a general notion of the author, I dedicated myself to reading the works “Critique of power” (1993), “Struggle for recognition: the moral grammar of social conflicts” (2015a), “Reification” (2018), “Suffering of indetermination ” (2007) and “The idea of socialism” (2017) and in specific texts such as “Pathologies of the social: The past and present of social Philosophy” (1996), “A Social Pathology of Reason: On the intellectual legacy of Critical Theory” (2004) and “The illnesses of society: Approaching an almost impossible concept” (2015c) to, in continuation, I present the debates of authors critical of Honneth's conceptions about social pathology. The work allowed me to observe that the expression of social pathology emerged in Honneth's work in different ways, with a predominant perspective related to the dysfunction of the social organism and the blockages of human flourishment.